Treatment of chronic tennis elbow by extracorporeal shock waves - Maier, M. (1997)
Dr. Markus Maier of the Gross Hadern Orthopaedic Clinic in Munich presented preliminary findings from a prospective study of treatment of chronic tennis elbow with extracorporeal shock waves (ESW). A total of 21 patients were treated from January to August 1996. In all cases, other treatments had proved unsuccessful in the preceding six months. ESW energy levels ranging from 0.03 to 0.11 mJ/mm2 were applied in three to four sessions, with 2,000 impulses in an 18 to 25-minute period on each occasion. After three to four sessions, a clinical improvement was recorded in all but four patients. No statistically significant data on the importance of factors such as the energy level, impulse rate or number of sessions were obtained. Larger prospective studies are needed, with a higher number of patients, to evaluate the factors influencing the clinical outcome, Dr. Maier said.